The Impact of Dermal Characteristics on Low-Level Laser Power Measurement in Postmortem Zoological Species - Faith Ramsey; Michelle Borsdorf; John Ladner; Anne White; Tara M. Harrison (Veterinary Medicine International)
Photobiomodulation therapy, also termed as low-level laser therapy, is commonly used as an adjunctive therapy for various medical conditions in veterinary practice. The ACTIVet PRO low-level laser has been used for treatment of various nondomestic species, yet the effects of dermal attributes such as pigment, feathers, or scales have not been evaluated. The effects of low-level laser therapy with the ACTIVet PRO have been investigated in laboratory animals, including a study in rats that evaluated the passage of laser light through the skin in postmortem samples. The objective of this study was to measure the power of a low-level laser (ACTIVet PRO) after penetration through dermal tissue (∼1 mm thickness) in a variety of postmortem animal tissue. This study sought to determine the impact of fur, feathers, scales, and different pigments on the ability of the laser to penetrate. Frozen and thawed skin tissue samples from various species were placed inside a light restricted laser box and exposed to a preprogrammed laser level from a Multi Radiance ACTIVet PRO photobiomodulation (PBM) device, with a power meter to measure the light penetration through the tissue samples. Light penetration measurements via power output measurements (mW) were recorded at 7 time points (range, 1–150 sec). A Friedman test was performed to evaluate the difference of the mean tissue penetration by each species at each time point. Lighter colored specimens had higher power readings than darker colored or pigmented samples, and feathers appeared to inhibit the laser, showing minimal to no power readings on bird skin covered in covert and down feathers. There was statistically significant mean tissue penetration for all time points between the rabbit and green sea turtle (p=0.0046), the red-tailed hawk and green iguana (p=0.0046), and the red-tailed hawk and green sea turtle (p=0.000034). Overall findings found that certain skin coverings, such as feathers, appear to inhibit passage of laser light through tissue to the photo meter. Darker pigmented areas of tissue appeared to absorb the laser light, which also did not allow light passage through the tissue to the photo meter. All of this illustrates that there are differences in tissue penetration between different animal species, at least in postmortem tissues. This could necessitate adjustment of machine settings for therapeutic effect in different species, though further studies would be warranted to determine the extent to which this would be necessary. Additional studies evaluating biologically active tissues would be needed as a next step, as photobiomodulation has an effect at the cellular level and the exact amount of medical benefit is not measurable in skin samples that are separate from a living organism.